Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Effective adsorption of zeolite/carbon composite molecular sieve synthesized from spent bleaching earth - Shixiang Zuo; Xiaoman Cao; Wenjie Liu; Tianhua Liu; Xiazhang Li; Chao Yao; Rong Xu; Yongsheng Fu (Environmental Science and Pollution Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)